2012
DOI: 10.1016/j.egypro.2012.05.061
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Earth-air Heat Exchangers for Low Energy Cooling of Buildings in South Algeria

Abstract: International audienceA one-dimensional steady numerical model is proposed to estimate the performance of earth-to-air heat exchangers, installed at different depth, used for building cooling/heating. Two parameters are considered to evaluate the performance of the system (Reynolds number and the form factor). With appropriate simplifications; Numerical simulation treatment is proposed to predict the temperature fields of the fluids in the pipe and the soil in the proximity of the buried pipe, taking into acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(29 citation statements)
references
References 5 publications
2
23
0
2
Order By: Relevance
“…From the authors' knowledge, few studies do not consider the convective coefficient as a known value. Sehli et al reported one of these studies [23].…”
mentioning
confidence: 96%
“…From the authors' knowledge, few studies do not consider the convective coefficient as a known value. Sehli et al reported one of these studies [23].…”
mentioning
confidence: 96%
“…Sehli et al proposed a one‐dimensional numerical model to check the performance of EAHEs installed at different depths. They concluded that EAHE systems alone are not sufficient to create thermal comfort but can be used to reduce the energy demand in buildings in South Algeria, if used in combination with conventional air‐conditioning systems.…”
Section: Introductionmentioning
confidence: 99%
“…EAHE performance for greenhouses was investigated in Turkey [5]. The potential of EAHE for low energy cooling of buildings in Algeria was investigated in [6]. The EAHEs were also investigated in France [7].…”
Section: Application Of Earth-to-air Heat Exchangersmentioning
confidence: 99%